A Numerical Method for Analyzing Electromagnetic Scattering Properties of a Moving Conducting Object - Lei Kuang; Shouzheng Zhu; Jianjun Gao; Zhengqi Zheng; Danan Dong (International Journal of Antennas and Propagation, 2014)
A novel numerical approach is developed to analyze electromagnetic scattering properties of a moving conducting object based on the finite-difference time-domain (FDTD) algorithm. Relativistic boundary conditions are implemented into the FDTD algorithm to calculate the electromagnetic field on the moving boundary. An improved technique is proposed to solve the scattered field in order to improve the computational efficiency and stability of solutions. The time-harmonic scattered field from a one-dimensional moving conducting surface is first simulated by the proposed approach. Numerical results show that the amplitude and frequency of the scattered field suffer a modulation shift. Then the transient scattered field is calculated, and broadband electromagnetic scattering properties of the moving conducting surface are obtained by the fast Fourier transform (FFT). Finally, the scattered field from a two-dimensional moving square cylinder is analyzed. The numerical results demonstrate the Doppler effect of a moving conducting object. The simulated results agree well with analytical results.